Tax Guide 2008-2009 - Sinclair, Walter; Lipkin, Barry (Palgrave Macmillan UK, 2008)
The 37th annual edition of the leading guide to taxation in Britain. This practical and user-friendly guide is a bestseller with students, professionals, accountants and private individuals, explaining in simple terms how the UK tax system works and how best to minimise tax liabilities